INDUSTRI PERBANKAN INDONESIA PERIODE 2001-2014: DETEKSI KONSENTRASI PASAR DAN PRESTASI ALMA - Jumono, Sapto; Achsani, Noer Azam; DB Hakim, DB Hakim; M Firdaus, M Firdaus (Jurnal Ekonomi : Journal of Economic, 2016)
This descriptive study aims to explain the condition of credits market and deposit market of Indonesian banking in the period of 2001-2014 includes the achievement of ALMA and CAMEL based on the secondary data and financial statements of 97 Indonesian banks. This graph result and tabulation and financial ratio show the information that Indonesian banking market is in the competitive condition (CR4 index and HHI index decrease and the market is classified in loose oligopoly condition), however all main variables of ALMA show the high ranking.Â Keywords: CR4,HHI, ALMA dan CAMEL